Interior Decoration to Exterior Surface: The Beleaguered Relief - Hedges, Susan (UI Scholars Hub, 2019)
Surface articulation is a critical issue for interior architecture, and this paper sees the wall as a point of intersection where art and structure may converge and collide. A place of experimentation and a site of performance, built volumes and surface embellishments blur and reinforce edge conditions and ornament as embellishment and essential structure merge. This paper explores a sculptural relief Copper Crystals (1965) constructed by Jim Allen for the ICI (Imperial Chemical Industries) House (1964) situated at 61 Molesworth Street in Wellington, New Zealand. Following the building's failure, due to a 7.8 magnitude earthquake, the sculptural relief survived a five thousand tonne demolition. Construction, size and position of the work have contributed to its survival, partly because the relief shifted from surface activation to structural member. This paper investigates the relief as it protrudes from the surface of the building’s interior. Surface, layer and structure extend beyond the planar, producing a range of complicated effects. Visible and invisible incrustations, geometric forms and structural matrices, transform and become linked to depth, substance, mass and thickness (Papapetros, 2013). The demarcation of the essential and inessential is blurred, and the perception of ornament as dangerous during earthquakes is subverted. This paper focusses on material mediation and points to new ways of interrogating the materiality and functionality of surface and places over time.